A GEOGRAPHICAL APPROACH TO SUSTAINABLE TERRITORIAL PLANNING - Margherita Ciervo (Bollettino della Società Geografica Italiana)
This paper explores an approach to territorial planning from a purely geographical perspective, with the idea to approach the top-down planning concept, similarly as if it were presented «bottom-up». The supporting thesis is that the geographical approaches (such as those proposed by the different addresses of this discipline) have the conceptual, interpretative and methodological tools to overcome, via a holistic and systemic outlook, the hierarchical and pyramidal formulation. Process, distribution and power relations are identified to recognize and explicate the subtended political choices, to get to the heart of problems. Building the foundations to develop a plan «with» the inhabitants, which are the communities that live in the place, and not solely «for» them. Another aim of this paper is to try to offer interpretative keys to «read» and/or evaluate and/or elaborate on participating planning policies (on different spatial scale levels) for a sustainable and ecological equilibrated government of territory.